Bioresource collection of blood components from pregnant women to identify fetal genetic features, as well as to search for genetic markers of gestational complications - E. S. Vashukova; O. A. Tarasenko; O. E. Talantova; P. Yu. Kozyulina; A. V. Morshneva; А. R. Maltseva; O. V. Pachulia; O. N. Bespalova; I. Yu. Kogan; A. S. Glotov (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To create collection of plasma and leukocyte blood samples from pregnant women to improve methods of non-invasive prenatal testing, as well as to search for deoxyribonucleic acid markers and study the molecular mechanisms of gestational complications.Material and methods. The collection creation process uses original standard operating procedures. The biomaterial for storage was plasma and leukocytes from the blood of pregnant women.Results. As of July 2023, the collection contains samples of blood plasma and buffy coat suspension from 5814 pregnant women. For 5692 women, whole- genome sequencing of extracellular deoxyribonucleic acid from blood plasma was performed on an Ion GeneStudio S5 system (Thermo Fisher Scientific Inc, USA). Data on cytogenetic examination of fetal material after invasive prenatal diagnosis were collected from 522 women. In 241 cases, samples were obtained from pregnant women with fetuses with a normal karyotype and in 282 cases from pregnant women with fetuses with chromosomal abnormalities. After pregnancy ended with childbirth, data on the course and outcomes of pregnancy were collected from 590 women. In 212 cases, pregnancy was complicated by great obstetrical syndromes. Based on the collection, a previously developed bioinformatic algorithm for non-invasive prenatal analysis was tested on a DNBSEQ-G50 sequencer (MGI, China). The obtained specificity corresponded to the expected one and was >99,9%. The sensitivity of the method is 100%.Conclusion. The created collection, as well as the clinical and genomic data associated with it, is a valuable resource for basic and applied research.